One-step method for improving the stability of coconut milk emulsion and keeping its flavor based on dynamic high-pressure microfluidization - DENG,Limei (2022)
Abstract Coconut milk is a traditional subtropical food, but its quality and flavor stability are the biggest challenge for promotion and commercialization. In this study, the effect of dynamic high-pressure microfluidization (DHPM) on texture and flavor properties of coconut milk was investigated under different pressures. The mean particle size decreased from 24.04 ± 1.17 μm (blank sample) to 8.21 ± 0.11 μm, reaching the minimum at 18000 psi. Microfluidization technique has positive effect on the taste of coconut milk, reducing the bitterness value from 13.39 ± 0.23 to 11.50 ± 0.20 (p > 0.05) using electronic tongue; simultaneously, the other tastes were retained. The flavor of coconut milk is less affected by pressure, and the flavor is essentially not lost in the appropriate pressure range. This work provides a new understanding of quality and flavor changes of coconut milk using DHPM in the future processing process.